L'escriptor, de llengua en llengua. Joan Fuster i les traduccions - Salvador, Vicent (Caplletra. Revista Internacional de Filologia, 2006)
This work approaches the study of the relationship between the figure of the translator and that of the writer in the framework of translating activities related to the Catalan language. In the person of Joan Fuster both sides are combined: he is an author translated into other languages, such as Spanish, English or Italian and he is, at the same time, a translator himself of European literary works, especially of Ignazio Silone and particularly Albert Camus. Both figures appear in the 20th century literature as an example of the intellectual who struggled among intellectual freedom and social and political commitment.The argument focuses on the active role Fuster had regarding the reception of European literature in the Catalan cultural area through the translations and selections he makes of a subject matter, central in his thinking of the fifties and sixties: the intellectual’s commitment. His text on Erasmus of Rotterdam is emblematic in this sense. The final question is about the current validity of Fuster’s reflections regarding translation into other languages.